Exploring the role of mast cells in the progression of liver disease - Huang, Shizhuan; Wu, Haotian; Luo, Feng; Zhang, Bin; Li, Tianwei; Yang, Zongrui; Ren, Bixuan; Yin, Wenze; Wu, Dehai; Tai, Sheng (Frontiers in Physiology, 2022)
In addition to being associated with allergic diseases, parasites, bacteria, and venoms, a growing body of research indicates that mast cells and their mediators can regulate liver disease progression. When mast cells are activated, they degranulate and release many mediators, such as histamine, tryptase, chymase, transforming growth factor-β1(TGF-β1), tumor necrosis factor–α(TNF-α), interleukins (ILs), cytokines, and other substances that mediate the progression of liver disease. This article reviews the role of mast cells and their secretory mediators in developing hepatitis, cirrhosis and hepatocellular carcinoma (HCC) and their essential role in immunotherapy. Targeting MC infiltration may be a novel therapeutic option for improving liver disease progression.